2019
DOI: 10.3390/jcm8081263
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sex Differences on Outcome after Major Trauma: Clinical Outcome in Women Versus Men

Abstract: Purpose: The purpose of this study was to evaluate epidemiological and clinically relevant sex-related differences in polytraumatized patients at a Level 1 Trauma Center. Methods: 646 adult patients (210 females and 436 males) who were classified as polytraumatized (at the point of admission) and treated at our Level I Trauma Center were reviewed and included in this study. Demographic data as well as mechanism of injury, injury severity, injury pattern, frequency of preclinical intubation, hemodynamic variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Gender, as another possible predictor of patients' outcomes and mortality in trauma patients, has been proposed by some studies. 23,24 Female gender might be associated with lower mortality and probability of admission to ICU. 25 In one study on blunt trauma patients, male patients were at a higher risk of mortality compared to female ones.…”
Section: Discussionmentioning
confidence: 99%
“…Gender, as another possible predictor of patients' outcomes and mortality in trauma patients, has been proposed by some studies. 23,24 Female gender might be associated with lower mortality and probability of admission to ICU. 25 In one study on blunt trauma patients, male patients were at a higher risk of mortality compared to female ones.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that the women are at risk for a prolonged in-hospital rehabilitation time after major trauma though there is an overall lower in-hospital mortality rate and increased likelihood for ICU admission. 59,60…”
Section: Gender and Polytraumamentioning
confidence: 99%